An Analysis of Attitudinal Resources in the Popular Thai Online Original Soundtrack,“Orchao-oey” (You) of the Period Soap Opera “Buppe San Nivas” (Love Destiny): Systemic Functional Linguistics and Appraisal Perspective - Preecha, Parinyaporn; Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Visual appraisal analysis has gained much attention from systemic functiona llinguists (Camelia et al,2016;Economou, 2009;Unsworth,‎2006) to discuss how images influence the multimodal texts and the visual and verbal appraisal systems are refined and extended (Ngo&Unworth, 2015). While such system addresses some aspects of visual semiosis, detailed analysis of attitudes is little studied in terms of images and verbal elements in a popular Thai period original soundtrack “Orchao-oey” (You) between February 2018 and April 2018, originated from the most famous soap opera, “Buppe San Nivas” (Lovedestiny). Therefore, this study analyses some distinctions of explicit visual inscription from a range of strategies for implicit invoking of attitudes in images underpinning the systemic functional linguistics and appraisal framework. The findings of the study reveal that the use of the distinctive affordances of visual, verbal resources and sound is much presented in the soundtrack concerned and appraisal resources of attitude which are mainly evoked visually and verbally. The study suggests some implications for further research in order to fulfill visual appraisal analysis and multimodal literacy pedagogies are also offered.